Housing affordability: A conceptual overview for house price index - Suhaida M.S.; Tawil N.M.; Hamzah N.; Che-Ani A.I.; Basri H.; Yuzainee M.Y. (2023)
Housing affordability research has been carried out by many as it is one of the key measures for a country's socio-economy stability. This research is carried out to identify possible application of affordability measures including Price-Income Ratio (PIR) for measurement of first owned medium cost landed-house by the middle-income group in Malaysia. It is hoped that it could be seen as able to contribute to the ground knowledge and understanding on housing affordability for the middle-income group and variables that influenced the medium income group's ability to own first medium-cost houses in Malaysia. 2011 Published by Elsevier Ltd.